2021
DOI: 10.1177/15691861211005059
|View full text |Cite
|
Sign up to set email alerts
|

The application of an information support robot to reduce agitation in an older adult with Alzheimer’s disease living alone in a community dwelling: a case study

Abstract: Objective/background: Agitation is a common behaviour of Alzheimer’s Disease (AD). Although healing robots have previously been used for alleviating agitation for people with dementia in hospitals and other healthcare facilities, its effects remain unclear whether an information-support robot capable of disseminating information with user needs may have similar effects when it is applied in community dwellings. This study was to investigate the effects of information-support robots for reducing agitation in ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The varied application of DATs can enhance cognitive abilities, as indicated by 34 studies. They demonstrated that patient monitoring,43 care support30 45 and digital therapeutics21–23 26–28 30 31 40 45 46 53–55 65 71 75 83–85 90 95 98 103 115–117 119–124 can lead to improvements in cognitive functioning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The varied application of DATs can enhance cognitive abilities, as indicated by 34 studies. They demonstrated that patient monitoring,43 care support30 45 and digital therapeutics21–23 26–28 30 31 40 45 46 53–55 65 71 75 83–85 90 95 98 103 115–117 119–124 can lead to improvements in cognitive functioning.…”
Section: Resultsmentioning
confidence: 99%
“…There are 12 BPSD, which include aberrant motor behaviour, agitation, anxiety, apathy, appetite changes, delusions, depression, disinhibition, elation/euphoria, hallucinations, irritability and sleep changes 125. Different BPSD were shown to be managed by DATs in 64 studies through digital therapeutics8 23 26–28 30 40 41 48 55 60 67–72 75 77 78 81–86 88 89 91–93 95 97–102 104 105 107 109 111–113 115–117 120 122–124 126–136 or by patient monitoring devices 30 48 69 86 93 98 133. All the DATS were reported to have a positive effect on BPSD.…”
Section: Resultsmentioning
confidence: 99%
“…The varied application of DATs can enhance cognitive abilities, as indicated by 34 studies. They demonstrated that patient monitoring [137], care support [53], [95], digital therapeutics [21], [23]- [26], [38], [39], [41], [44], [51], [53], [55], [58], [60], [61], [64], [65], [67], [69], [70], [72], [74], [76], [87], [93], [95], [98]- [100], [123], [124], [134], [138] can lead to improvements in cognitive functioning.…”
Section: Improving Cognitionmentioning
confidence: 99%
“…Rather, we focus on evaluating the performance of clustering primitive patterns in sequences of binary sensor signals under as few assumptions as possible, because the basic clustering performance is an important first step in a complex activity analysis. Also, clustering can be directly used to evaluate the quantity and quality of primitive activities, such as the restlessness behavior of patients with Alzheimer's disease [22]. To this end, we evaluated the performance of clustering activities corresponding to short time periods using various generative models for sensor signals as well as the k-means method, a typical clustering method, and frequent sequence mining [8] previously used in activity discovery other than generative models.…”
Section: Introductionmentioning
confidence: 99%